Exploring Early Childhood Interests and Talents Through Role-Play Methods - Misbayani Misbayani; Akbar Iskandar; Kumar Vivek (Jurnal Abdimas Cendekiawan Indonesia, 2024)
Children's interests and talents are two very important things to develop from an early age. Both can be the foundation for children's future development, both in academic and non-academic fields. One effective method to explore children's interests and talents is through role-playing. This method is not only fun for children, but also full of educational benefits. Exploring children's talents and understanding their potential from an early age is the key to helping them grow and develop optimally. Children have their own world full of curiosity and uniqueness, through observation and deep understanding of their responses and behavior. We can find valuable clues about the interests and talents they are born with. Providing freedom to explore and the opportunity to try various activities is an effective way to help children find their own interests and talents. This process is not only about finding a particular talent but also about building self-confidence and the ability to adapt to various situations. In the role-playing method, the themes that can be given are themes that are close to the child's world, such as family and profession through these themes, role-playing will be more effective because children know and directly play the characters they will play and children will interact with other friends. So that social development can be honed to the maximum.